2018
DOI: 10.1039/c8lc00636a
|View full text |Cite
|
Sign up to set email alerts
|

An integrated micro-millifluidic processing system

Abstract: An integrated micro-millifluidic processing system based on multimaterial 3D-printing and a maskless lithography system is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…The smallest feature sizes are achieved using microstereolithography, 11 modied 3D printers and resins, 24 and high-end or custom 3D printers. 14,16,25,26 Channel sizes down to 18 Â 20 mm have been reported with custom setups. 25 Smaller channel sizes are more difficult to obtain with commercial desktop printers.…”
Section: Introductionmentioning
confidence: 99%
“…The smallest feature sizes are achieved using microstereolithography, 11 modied 3D printers and resins, 24 and high-end or custom 3D printers. 14,16,25,26 Channel sizes down to 18 Â 20 mm have been reported with custom setups. 25 Smaller channel sizes are more difficult to obtain with commercial desktop printers.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, manipulation of droplets in 3D-printed devices including droplet coalescence and sorting has started to be reported. Zhang et al [83] printed a monolithic sorting junction embedded with valves via multimaterial printing (Figure 9(2)). Through pneumatic control of valves to tune the flow resistance, droplet can be sorted into the desired channel.…”
Section: 3dp Droplet Microfluidicsmentioning
confidence: 99%
“…Cecil et al [84] also integrated LED on a 3D-printed device for photometric detection. Recently, Zhang et al [83] reported an integrated micro-millifluidic processing system which was manufactured by multimaterial 3DP (Figure 10(3)). Droplet generation, detection, sorting and collection can be achieved in their complex system, which shows 3DP great potentials in developing complicated and integrated system for droplet control.…”
Section: 3dp Droplet Microfluidicsmentioning
confidence: 99%
See 2 more Smart Citations